2021
DOI: 10.1073/pnas.2100707118
|View full text |Cite
|
Sign up to set email alerts
|

Surviving winter on the Qinghai-Tibetan Plateau: Pikas suppress energy demands and exploit yak feces to survive winter

Abstract: The Qinghai-Tibetan Plateau, with low precipitation, low oxygen partial pressure, and temperatures routinely dropping below −30 °C in winter, presents several physiological challenges to its fauna. Yet it is home to many endemic mammalian species, including the plateau pika (Ochotona curzoniae). How these small animals that are incapable of hibernation survive the winter is an enigma. Measurements of daily energy expenditure (DEE) using the doubly labeled water method show that pikas suppress their DEE during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 99 publications
1
61
0
Order By: Relevance
“…It inhabits the alpine regions at an altitude of 3,100–5,300 m above sea level and is well adapted to extreme hypoxia, cold, and food deprived environments ( Cao et al, 2017 ). In this scenario, plateau animals including plateau pika face severe energetic challenges to maintain their core body temperature ( Van Sant and Hammond, 2008 ; Zhang et al, 2012 ; Speakman et al, 2021 ). Previous studies have found that at different altitudes, the life history strategies and personalities of plateau pika varied significantly ( Liu et al, 2012 ; Qu et al, 2013 ; Qu et al, 2019 ; Tan et al, 2020 ), accompanied by differences in fat accumulation and metabolic rate ( Yang et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…It inhabits the alpine regions at an altitude of 3,100–5,300 m above sea level and is well adapted to extreme hypoxia, cold, and food deprived environments ( Cao et al, 2017 ). In this scenario, plateau animals including plateau pika face severe energetic challenges to maintain their core body temperature ( Van Sant and Hammond, 2008 ; Zhang et al, 2012 ; Speakman et al, 2021 ). Previous studies have found that at different altitudes, the life history strategies and personalities of plateau pika varied significantly ( Liu et al, 2012 ; Qu et al, 2013 ; Qu et al, 2019 ; Tan et al, 2020 ), accompanied by differences in fat accumulation and metabolic rate ( Yang et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that horizontal transmission significantly increases microbial diversity [ 44 ] and that the host acquires gut microbiota from other species to maintain a significantly greater species richness and biodiversity than non-gut environments [ 45 , 46 ]. Moreover, pikas eat the feces of yaks [ 24 , 47 ], which could increase the gut microbial diversity of pikas that live with yaks. Likewise, the soil-ingestion behavior of yaks may increase their gut microbial diversity when they live with pikas, as pikas excrete hard solid fecal pellets throughout the field [ 3 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, another interpretation is that the stronger tolerance to toxic plant secondary metabolites (PSMs) of plateau pikas, compared with that of other herbivores, results in its outbreak in degraded regions, which are widely colonized by poisonous plants [ 21 , 22 , 23 ]. However, we have found that plateau pikas survive in winter by eating yak feces when food is short, and horizontal transmission of gut microbiota occurred during this process [ 24 ]; these scenes made us question if pikas eat yak feces in summer, or if horizontal transmission of gut microbiota also occurred in summer.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with NTXJ, throughout other alpine meadows, or grassland areas in the world [51][52][53], longer grazing durations may indeed have a more significant impact on the population density of rodents. In addition, in alpine meadows, small rodents such as pika may spend the winter by eating yak feces [54], so the population density and grazing intensity may also show a positive correlation.…”
Section: Other Potential Impacts Of Grazing On Rhdmentioning
confidence: 99%